Konsep Adab dalam Pendidikan Karakter: Implementasi Pemikiran Syed Naquib Al-attas di Lembaga Pendidikan Islam - Kalam Mahardika; Indah Cendikia Nasution; Mutimmatuz Zahro; Syamsul Arifin (Civiliza Publishing, Indonesia., 2026)
The moral crisis and character deterioration in the world of education today are rooted in the loss of the value of manners in the learning process. This research aims to explore the urgency of adab as the main foundation of character education through the view of Syed Muhammad Naquib Al-Attas. Al-Attas emphasized that the main problem of modern Muslims is not in science and technology but in the loss of adab, which has implications for the chaos of knowledge and the birth of unworthy leaders. This research method uses a qualitative approach with the type of library research. The data were analyzed descriptive-analytically on the main works of Al-Attas on the concept of ta'dib. The results of the study show that in Al-Attas's perspective, education is not just a transfer of knowledge, but the cultivation of adab which includes recognition and acknowledgement as well as awareness of one's abilities and potential, intellect and spirituality towards existing forms and knowledge. The implementation of Al-Attas' thought in Islamic educational institutions demands the integration of intellectual intelligence and spiritual integrity. The findings of the study emphasize that effective character education can only be achieved if educational institutions are able to reactualize the concept of ta'dib, where educators become a mirror of civilization and the curriculum is arranged based on the correct hierarchy of knowledge. Thus, adab is not just a courtesy and complement to the curriculum, but the spirit of the entire process of Islamic education.